Characterization and cytotoxic activity of ribotoxin-like proteins from the edible mushroom Pleurotus eryngii. (1st December 2022) - Landi, Nicola; Grundner, Maja; Ragucci, Sara; Pavšič, Miha; Mravinec, Martina; Pedone, Paolo V.; Sepčić, Kristina; Di Maro, Antimo
Graphical abstract: Highlights: Pleurotus eryngii fruiting bodies harbour 4 ribotoxin-like proteins, eryngitins 1–4. Enzymatic and structural features of eryngitins were investigated. Eryngitins 1–4 are quickly hydrolysed by in vitro digestion system. Eryngitins 1–4 are cytotoxic for Sf9 insect cells and not cytotoxic for HUVEC cells. Cytotoxicity is not altered upon addition of aegerolysin-based cytolytic complexes. Eryngitins 1–4 are probably part of mushroom defence system against insects. Abstract: Ribotoxin-like proteins (RL-Ps) represent a novel specific ribonuclease family found in edible mushrooms and are able to inhibit protein synthesis. Here, we report the characterization and cytotoxic effects of four novel RL-Ps, named eryngitins, isolated from fruiting bodies of the king oyster mushroom ( Pleurotus eryngii ). These proteins induced formation of α-fragment from rabbit ribosomes, characteristic of their enzymatic action. The two 15 kDa eryngitins (3 and 4) are considerably more thermostable than the 21 kDa ones (1 and 2), however their overall structural features, as determined by far-UV CD spectrometry, are similar. Complete in vitro digestibility by pepsin-trypsin, and lack of cytotoxicity towards human HUVEC cells suggest low toxicity of eryngitins, if ingested. However, eryngitins exhibit cytotoxic action against insect Sf9 cells, suggesting their possible use in biotechnological applications as bioinsecticides. This cytotoxicity was not enhanced in the presence of cytolytic protein complexes based on aegerolysin proteins from Pleurotus mushrooms.